Innocent of the crime under investigation: suspects’ counter-interrogation strategies and statement-evidence inconsistency in strategic vs. non-strategic interviews - Clemens, Franziska (Psychology, crime & law, 2019)
The study examines the counter-interrogation strategies applied by mock suspects (N = 94), who are innocent of a mock crime under investigation but who were present at the scene, for different reasons, at around the time the crime occurred. Half were present at the crime scene to carry out a lawful act, the other half to carry out an unlawful act. Furthermore, this study examines the effect of the Strategic Use of Evidence (SUE) technique as a strategic interviewing technique (vs. a non-strategic technique), on suspects’ statement-evidence inconsistencies. Participants were randomly assigned to the two interview conditions (strategic vs. non-strategic) and were interviewed as suspects of a crime, which none of them had committed. The results show that the most commonly used counter-interrogation strategy in both groups was to be honest. However, 26.1% of the innocent suspects, performing an unlawful act, reported the strategy to be deceptive. In addition, the statements of suspects executing an unlawful act were significantly more inconsistent with the evidence in the strategic than the non-strategic interview condition. The increased statement-evidence inconsistency rates potentially put these suspects at risk of being assessed as guilty of a crime they did not commit.